Hypomethylation of PRDM1 is associated with recurrent pregnancy loss. Issue 12 (29th April 2020) - Du, Guizhen; Yu, Mingming; Xu, Qiaoqiao; Huang, Zhenyao; Huang, Xiaomin; Han, Li; Fan, Yun; Zhang, Yan; Wang, Ruohan; Xu, Shuyu; Han, Xiumei; Fu, Guangbo; et al.
Abstract: Recurrent pregnancy loss (RPL) rates have continued to rise during the last few decades, yet the underlying mechanisms remain poorly understood. An emerging area of interest is the mediation of gene expression by DNA methylation during early pregnancy. Here, genome‐wide DNA methylation from placental villi was profiled in both RPL patients and controls. Subsequently, differentially expressed genes were analysed for changes in gene expression. Many significant differentially methylated regions (DMRs) were identified near genes dysregulated in RPL including PRDM1 . Differentially expressed genes were enriched in immune response pathways indicating that abnormal immune regulation contributes to RPL. Integrated analysis of DNA methylome and transcriptome demonstrated that the expression level of PRDM1 is fine‐tuned by DNA methylation. Specifically, hypomethylation near the transcription start site of PRDM1 can recruit other transcription factors, like FOXA1 and GATA2, leading to up‐regulation of gene expression and resulting in changes to trophoblast cell apoptosis and migration. These phenotypic differences may be involved in RPL. Overall, our study provides new insights into PRDM1 ‐dependent regulatory effects during RPL and suggests both a mechanistic link between changes in PRDM1 expression, as well as a role for PRDM1 methylation as a potential biomarker for RPL diagnosis.